FACTORS INFLUENCING THE RETENTION OF GENERATION Y EMPLOYEES IN THAILAND (Proceedings of the International Conference on Education, 2022)
Generation Y or the Millennial can be classified as persons born between the early 1980s and 2000s, and they have fully entered the workforce and represent the future leaders of the organization. Several literatures; however, dubbed the Millennials as the job-hopping generation due to their preference to explore new career opportunities rather than remaining with one particular organization for life. This research explores and analyzes the factors influencing Generation Y employees to remain with the organization in Thailand by using the Two-factor theory and the Job embeddedness theory. To gain a clear insight into the mind of Generation Y employees, this research employs a mixed method of online quantitative survey and qualitative thematic analysis of interviews. An online questionnaire was given to 100 samples of millennials living in Thailand focusing on demographic and exploring factors deemed vital to their consideration of choosing to remain with employers. Statistical key findings were generated via then explored further in an in-depth interview. The findings show that all four factors regarding motivator factors, hygiene factors, on-the-job embeddedness factors, and off-the-job embeddedness factors have positive impacts on employee retention among Thai Generation Y as they are motivated to prefer employers and work environment that address and satisfy them in these concerns over the sense of loyalty. Meanwhile; the elements of compensation, training and development, work environment, community links (family) are the top issues that strengthen or lessen employees’ intention to stay with the company.
Keywords: Generation Y; millennial; employee retention; employee motivation